العُدّ الشائع وعلاقته بالعادات الغذائية - رومية, عبد الحليم; عبد الهادي, نيفين (Latakia University Journal -Medical Sciences Series, 2014)
شملت الدراسة 198 مريضاً مصاب بالعد تراوحت أعمارهم بين 11-35 سنة، توزعوا بحسب شدة العد سريرياً بين الخفيف(30.30%) والمتوسط(44.44%) والشديد(25.25%)، وقد تمّ اختيار مجموعة من 50 شخصاً غير مصاب بالعد واعتمدت كمجموعة شاهد. خُصّص لكل مريض استمارة خاصة ثم تم جمع البيانات من الاستمارات حول الاستهلاك المتكرر لبعض المواد الغذائية. أوضحت دراستنا الترابط بين الاستهلاك المتكرر لكل من (منتجات الألبان، الأطعمة المقلية ، الحلوى والأغذية ذات المحتوى المرتفع من السكريات ، الشوكولا ) وزيادة احتمال الإصابة بالعد. بينما لم يُثبت وجود علاقة بين زيادة تناول البيض ،المكسرات والأغذية الدهنية وحدوث المرض. لكن أظهرت دراستنا أن زيادة تناول كل من (منتجات الألبان، البيض، الحلوى ،السكريات، الأغذية الدهنية والمقلية ) قد تكون عوامل مفاقمة للعد حيث ترافقت زيادة استهلاكها مع الحالات الأكثر شدة من المرض، بينما لم يلاحظ هذا الارتباط مع الشوكولا والمكسرات. كما بينت دراستنا أهمية الاستهلاك المرتفع لكل من (الخضار ، الفاكهة ، الأسماك والمؤكولات البحرية) كعامل وقاية جيد. This study included 198 patients who were divided into groups according the clinical severity of acne: mild (30.30%), moderate (44.44%), severe acne (25.25%). We chose 50 persons who did not have acne and depended on them as a control group. Our study showed the correlation between high and frequent consumption of certain food stuff (milk, dairy products, fried food, sweets and food with a high content of sugars, chocolate) and the increase in the risk of occurrence acne. We could not prove the existence of a relationship between frequent intake of (eggs, fatty food, nuts) and the incidence of the disease. But the study showed that increased intake of each of the (dairy products, eggs, sweets, sugars, and food high in fat and fried) may be exacerbating factors the disease, because increased consumption was accompanied by more severe cases of the disease. But we did not notice this link with chocolate and nuts. Our study also showed the importance of the high consumption of each (fruit, vegetables, fish and marine products) as a prevention of occurrence acne, and the lack of consumption increase the probability of appearance the disease.